Decision making in surgical oncology. - Lamb, B; Green, J; Vincent, C; Sevdalis, N (2011)
Decisions in surgical oncology are increasingly being made by multi-disciplinary teams (MDTs). Although MDTs have been widely accepted as the preferred model for cancer service delivery, the process of decision making has not been well described and there is little evidence pointing to the ideal structure of an MDT. Performance in surgery has been shown to depend on non-technical skills, such as decision making, as well as patient factors and the technical skills of the healthcare team. Application of this systems approach to MDT working allows the identification of factors that affect the quality of decision making for cancer patients. In this article we review the literature on decision making in surgical oncology and by drawing from the systems approach to surgical performance we provide a framework for understanding the process of decision making in MDTs. Technical factors that affect decision making include the information about patients, robust ICT and video-conferencing equipment, a minimum dataset with expert review of radiological and pathological information, implementation and recording of the MDTs decision. Non-technical factors with an impact on decision making include attendance of team members at meetings, leadership, teamwork, open discussion, consensus on decisions and communication with patients and primary care. Optimising these factors will strengthen the decision making process and raise the quality of care for cancer patients.